Predisposing and Precipitating Risk Factors for Delirium in Elderly Patients Admitted to a Cardiology Ward: An Observational Cohort Study in 1,042 Patients - Zipser, Carl Moritz; Hildenbrand, Florian Freimut; Haubner, Bernhard; Deuel, Jeremy; Ernst, Jutta; Petry, Heidi; Schubert, Maria; Jordan, Katja-Daniela; von Känel, Roland; Boettger, Soenke (Frontiers in Cardiovascular Medicine, 2021)
Aim: Although the risk factors for delirium in general medicine are well-established, their significance in cardiac diseases remains to be determined. Therefore, we evaluated the predisposing and precipitating risk factors in patients hospitalized with acute and chronic heart disease. Methods and results: In this observational cohort study, 1,042 elderly patients (≥65 years) admitted to cardiology wards, 167 with and 875 without delirium, were included. The relevant sociodemographic, cardiac- and medical- related clusters were assessed by simple and multiple regression analyses and prediction models evaluating their association with delirium. The prevalence of delirium was 16.0%. Delirious patients were older (mean 80 vs. 76 years; p<0.001) and more often institutionalized prior to admission (3.6 vs. 1.4%, p=0.05), hospitalized twice as long (12±10 days vs. 7±7 days; p<0.001), and discharged more often to nursing homes (4.8% vs. 0.6%, p<0.001), or deceased (OR 2.99, CI 1.53-5.85, p=0.003). Most relevant risk factors were dementia (OR 18.11, 5.77-56.83, <0.001), followed by history of stroke (OR 6.61, 95% CI 1.35-32.44, p=0.020), and pressure ulcers (OR 3.62, 95% CI 1.06-12.35, p=0.040). The predicted probability for developing delirium was highest in patients with reduced mobility and institutionalization prior to admission (PP=31.2%, p=0.001). Of the cardiac diseases, only valvular heart disease (OR 1.57, 95% CI 1.01-2.44, p=0.044) significantly predicted delirium. Patients undergoing cardiac interventions did not have higher rates of delirium (OR 1.39, 95% CI 0.91-2.12, p=0.124). Conclusion: In patients admitted to a cardiology ward, age-related functional and cognitive impairment, history of stroke, and pressure ulcers were most relevant risk factors for delirium. With regards to specific cardiological factors, only valvular heart disease was associated with risk for delirium. Knowing these factors can help cardiologists to facilitate the early detection and management of delirium.